The use of monoclonal antibody (Rituximab) in the treatment of type II mixed cryoglobulinemia - Rego,Thiago Carlos Gonçalves (2007)
Anti-CD20 monoclonal antibody has been successfully used to treat several self-immune diseases. The authors report the case of a 71 year-old female patient under the use of pegylated form of interferon á associated with ribavirin for the treatment of hepatitis C, who, after concluding the therapeutic program - negative Polymerase Chain Reaction (PCR) - developed a severe cutaneous vasculitis, receiving the diagnostic of type II mixed cryoglobulinemia. Four sessions of plasmapheresis were prescribed along the period of 11 days, with no result. The choice made was to administer anti-CD 20 monoclonal antibody (rituximab), 375 mg/m², per week, during four consecutive weeks. One could observe fast recovery from the purpura, as well as total remission of urticaria.